CONTENTS OF ANGIOGENIC GROWTH FACTORS IN THE PATIENTS WITH LOCAL FROSTBITES - K. G. Shapovalov; V. A. Sizonenko; Yu. A. Vitkovsky (Медицинская иммунология)
Abstract. The aim was to study the contents TGFα, TGFβ1 and VEGF in blood of patients with local frostbites. 50 men with local frostbites of extremities (II-IV degree) in the age up to 17-45 years old were examined. The patients were classified depending on the time elapsing post-lesion (group 1, early reactive period; group 2, late reactive period; group 3, granulation and epithelization of lesions). Quantitative determination of TGFα, TGFβ1 and VEGF in blood was performed by ELISA techniques. Blood samples were taken at early, late reactive periods and at period of epithelization of local frostbites. It was revealed that the contents of TGFα, TGFβ1 and VEGF were increased in patients’ blood at later terms after local frostbites. VEGF contents in blood of the frostbite patients increased to higher degrees than the values of TGFα and TGFβ1. An imbalance between TGFα, TGFβ1 and VEGF contents in frostbites was observed in cases of lagging repair and unfavorable clinical course. (Med. Immunol., vol. 10, N 4-5, pp 483-485).